Penerapan Akuntansi Keberlanjutan Berbasis ESG (Environmental, Social and Governance) pada Arah Coffee Shop Modern di Surabaya - Hilda Nabighoh Hafsha; Maria Carolla Jenniver Ati; Titiek Rachmawati (Jurnal Nirta : Inovasi Multidisiplin, 2026)
The development of modern coffee shops in Surabaya reflects changes in people’s lifestyles, where cafés are no longer only places to enjoy beverages, but also spaces for working, studying, and socializing. This condition encourages business owners not only to focus on profit, but also to pay attention to business sustainability through the implementation of Environmental, Social, and Governance (ESG) principles. This study aims to analyze the implementation of sustainability accounting based on ESG in modern coffee shops in Surabaya. The novelty of this research lies in examining ESG implementation in the modern coffee shop sector from the perspective of sustainability accounting, which is still rarely discussed. This study employed a qualitative descriptive method with a case study approach at ARAH Coffee Neo Lumina Surabaya. Data were collected through direct observation, informal interviews, documentation, and literature study. The data analysis technique was conducted descriptively by classifying findings based on environmental, social, and governance aspects. The results indicate that the environmental aspect is reflected in business area cleanliness, facility management, and environmental comfort. The social aspect is reflected in customer service, supporting facilities, and the creation of social interaction spaces. The governance aspect is reflected in the use of digital payment systems and operational management. This study concludes that modern coffee shops have implemented ESG principles fairly well, although continuous improvement is still needed to enhance competitiveness and business sustainability.